2015
DOI: 10.1007/s00280-015-2749-0
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol sensitizes the antitumor activity of 5-FU through down-regulation of thymidylate synthase in human colon carcinoma cells

Abstract: These findings suggest that gossypol-mediated down-regulation of TS, cyclin D1, and the mTOR/p70S6K1 signaling pathways enhances the anti-tumor effect of 5-FU. Ultimately, our data exposed a new action for gossypol as an enhancer of 5-FU-induced cell growth suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Studies in cancer cell lines have shown an inverse relation between TS expression and efficacy of 5-FU treatment. 30,31 The expression of TP and DPD was markedly altered by the presence of inflammation. Areas of inflammation in the cyst wall were seen in most cases (10 of 14) in this study and were likely induced by prior incisional biopsy examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cancer cell lines have shown an inverse relation between TS expression and efficacy of 5-FU treatment. 30,31 The expression of TP and DPD was markedly altered by the presence of inflammation. Areas of inflammation in the cyst wall were seen in most cases (10 of 14) in this study and were likely induced by prior incisional biopsy examination.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Downregulation of TS results in increased efficacy of 5-FU in colorectal cancer cell lines. 31 DPD is an enzyme involved in uracil and thymidine catabolism and is responsible for the breakdown of 5-FU into its excretory metabolites. 32 Low expres-sion of DPD suggests an improved response to 5-FU treatment because DPD is used to break down 5-FU.…”
mentioning
confidence: 99%
“…34 On the other hand, the Bcl-2 family proteins may not be the major targets of AT-101 in some patients. Indeed, gossypol has been reported to affect many other proteins or pathways, such as inhibiting mitosis, cyclin D1, and Rb, 44 decreasing ATP synthesis related with aldehyde dehydrogenase, 45 suppressing the mTOR/p70S6K1 signalling pathway, 46 downregulating phospholipase A2 to induce endoplasmic reticulum stress, 47 and interacting with intracellular copper to generate reactive oxygen species (ROS). 48 Furthermore, the polyphenol structure of gossypol might contribute to its multi-target properties in cells, and thus has received a great deal of attention from medicinal chemists.…”
Section: Gossypol: a Potential Anti-cancer Drug Candidate With A Varimentioning
confidence: 99%
“…Also, it inhibits CRC growth in a mouse xenograft model after oral administration (Zhang et al, 2003; Lan et al, 2015). Gossypol sensitizes the antitumor activity of 5-FU, causing a synergistic cytotoxic effect in HT-29, HCT116, and RKO cells, compared with monotherapies (Table 3; Yang D. et al, 2015). …”
Section: Gossypolmentioning
confidence: 99%